A Verbal/Social Autopsy (VASA) child mortality inquiry to investigate under-five mortality determinants in slums of Karachi, Pakistan: A Mix Methods Interventional Study - Siddiqui, Muhammad Bilal; Wan Ng, Chiu; Wah Yun Low; SherShah Syed; Ahmed , Sadaf; Noushad , Shamoon; Ali, Alvira; Kisa Fatima; Mirza, Maria (International Journal of Endorsing Health Science Research, 2016)
Background: Pakistan stands along top ten countries responsible for two-third of global child mortality burden. To improve Child Mortality (CM) estimates in Pakistan, there is an exigent need to understand the in-depth reasoning behind mortalities. In Pakistan, the data on cause-of-death (CoD) for a large number of child mortalities in Pakistan is either not available or not suitable for use. Pakistan uses an alternative technique called Verbal autopsy (VA). Since VA only determines the biological cause of death (BCoD), and does not capture multitude of other modifiable social, cultural and health system determinants, it has a limited importance. Such non-biological determinants are captured by another technique i.e. Social Autopsy (SA). Objective: By integrating VA with SA, extended set of mortality related determinants will be explored, in addition to strengthening death notification coverage and assigning CoD in such missed out mortalities. Method: Under the working group of Health Advocacy Council for Women and Children (HACWC) in collaboration with Child Registry of Pakistan (CROP), mixed method (QUAN-QUAL) interventional study will be carried out in urban-slums of Karachi city using VASA-integrated under-five mortality investigative technique. Parents of dead children will be interviewed. Second stage of study will be followed by qualitative interviews with different cadres of stakeholders. Expected Outcomes: By focusing the specific determinants related to case-management and care-seeking process (identified by The Pathway to Survival Framework-TPtoSF) an in-depth understanding of related determinants can be achieved, which will help in crafting potential interventions required to limit the barriers that increase the chances of CM in developing nations.